2022
DOI: 10.1001/jamanetworkopen.2022.16281
|View full text |Cite
|
Sign up to set email alerts
|

Looking Beneath the Surface: Racial Bias in the Treatment and Management of Pain

Abstract: Research has consistently documented inequities in the quality of care experienced by Black patients, with negative downstream effects on patient outcomes. Chronic pain is an area where substantial racial and ethnic differences in the management and treatment of Black individuals' pain have been well-documented. While previous research posits that the patient-physician relationship is a primary mechanism for these disparities, little empirical research has examined this association.The study by Licciardone et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Several disparities identified in this dataset are well-documented in patient populations not specific to endometriosis (e.g. prescriptions of antidepressants 28,29 , select anxiolytics 30 , and pain medication [8][9][10][11] ). Prior studies have also observed racial disparities in endometriosis diagnosis 6 and surgical treatments 7 ; therefore, it becomes important to consider how lack of treatment and lack of diagnosis may collectively impact patients' healthcare experiences.…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 96%
“…Several disparities identified in this dataset are well-documented in patient populations not specific to endometriosis (e.g. prescriptions of antidepressants 28,29 , select anxiolytics 30 , and pain medication [8][9][10][11] ). Prior studies have also observed racial disparities in endometriosis diagnosis 6 and surgical treatments 7 ; therefore, it becomes important to consider how lack of treatment and lack of diagnosis may collectively impact patients' healthcare experiences.…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 96%
“…Such approaches implicitly treat that clinical assessment as the ground truth, and in so doing establish contemporary clinician-level performance as a ceiling. This is problematic given the well-documented fallibility of human clinicians [87], and the pervasive biases which further worsen the quality of care for underserved patients [88,89]. While learning from clinicians (particularly ensembles of clinicians) is important, MLHC should strive where possible to surpass the quality and accuracy of existing clinical practice.…”
Section: Moving Past the Status Quomentioning
confidence: 99%
“…Many still think Black people feel less pain than they do (Akinlade 2020; Anderson, Green, and Payne 2009; Schoenthaler and Williams 2022). Through an intersectional lens, Black women often suffer exponential harm.…”
Section: The Middle Fingermentioning
confidence: 99%